The fast and the furious. Tokyo drift [videorecording (DVD)] - Lin, Justin; Black, Lucas, 1982-; Bow Wow (Musician); Tee, Brian (Fast and the furious (Motion picture), 2011)
To avoid jail time, street racer Sean Boswell is sent to live with his father, who is in the military and serving in Tokyo. There he discovers drift racing. After losing a race to Yakuza-connected D.K., the Drift King, Sean has to enter the Tokyo underworld to find a way to pay his debt.